WOMEN IN A DIGITIZED SPORTS CULTURE Nordic perspectives. (ROUTLEDGE, 2025)
This book provides important new insights into the interplay between gender, technology, sport, and media in the Nordic context, offering a deeper understanding of how digitalization affects sports practices, values, and structures.Bringing together leading experts and a mix of young and senior scholars from Denmark, Finland, Norway and Sweden, this book presents new empirical research and critical theoretical perspectives on topics ranging from athletes' self-presentation and community building in social media to technological innovation and changing working conditions in the sports sector. Despite the famously high scores for gender equity and digitization across society within the Nordic countries, Nordic women actors in sport still face serious challenges being embedded in historically shaped structures of inequality and hegemonies of masculinity dominant in sport. This book looks at how waves of mediatization are affecting different groups of women sports professionals: athletes, coaches, referees, and journalists. Drawing on work from sociology, media and communication studies, cultural studies and gender studies, this book considers the processes by which new technologies and digital media are saturating everyday sporting practices and shaping the professional lives and careers of women in sport. It expands our understanding of sport and social issues in Nordic society, of the Nordic model of sport, and of how intersections of gender, digital technology and media impact on sport everywhere.This is essential reading for all researchers, students and sports practitioners interested in sport, gender, media, technology and society.